Durable complete response for oligometastatic renal cell carcinoma with immune checkpoint inhibition and cytoreductive nephrectomy in a Jehovah’s witness: A case report - Zhuang, Tony Zibo; Harik, Lara; Force, Seth; Hadadi, Agreen; Bilen, Mehmet Asim; Brown, Jacqueline T.; Carthon, Bradley C.; Goldman, Jamie; Kucuk, Omer; Master, Viraj A.; Nazha, Bassel (Frontiers in Oncology, 2022)
The role of cytoreductive nephrectomy in patients with metastatic renal cell carcinoma is a subject of debate. We report a durable complete response in a 62-year-old man Jehovah’s Witness with metastatic clear cell renal cell carcinoma who received 2 cycles of nivolumab/ipilimumab followed by radical nephrectomy and metastectomy of known pulmonary disease site, both without a clinical need for perioperative blood transfusions. The patient continues to be without evidence of disease and without additional need for systemic therapy over a year after his radical nephrectomy. The case highlights that cytoreductive nephrectomy continues to play a role in the era of immune checkpoint inhibitors.